OR03-04 The Study of Cell Senescence in Cortisol-Producing Adrenocortical Adenomas - Gao, Xin (J Endocr Soc, 2020)
Introduction Aging is associated with the pathogenesis of many endocrine disorders such as cardiovascular diseases and diabetes. Cell senescence has been reported as one of their mechanisms. In addition, stress responsiveness has been reported to be associated with cell senescence. In addition, some genetic abnormalities such as mitochondrial DNA (mtDNA) damages or telomere shortening, have been detected in some endocrine disorders. Cortisol is a well-known stress-induced hormone and closely associated with aging. We previously reported that cortisol-producing adenoma (CPA) more abundantly expressed cell senescent markers such as p16 and p21 than other hormone-producing adrenocortical adenomas. However, the detailed pathophysiology of cell senescence and its association with histological features in CPAs have remained virtually unknown. Therefore, we analyzed cell senescent markers (telomere length, mtDNA copy number, mtDNA deletion and p16 and p21 immunoreactivity) and analyzed their correlation with clinicopathological factors in CPA patients. Methods & Materials Forty CPA cases was immunohistochemically evaluated. Twenty CPA, ten adjacent ZF and six non-functional adenoma (NFA) were examined for mtDNA abnormalities. mtDNA deletion was evaluated by nested-PCR and mtDNA copy number and telomere length were measured using real-time PCR. Results p21 immunoreactivity was significantly higher in CPA than that of adjacent ZF (P=0.0001) and significantly inversely correlated with tumor size (P=0.0004). Telomere length was much longer in CPA than that in adjacent ZF(P=0.0038), and NFA (P=0.0018). mtDNA copy number of NFA was significantly higher than that of CPA and adjacent ZF (P=0.0038). mtDNA copy number of compact cells was significantly higher than that of clear cells (P=0.0432). mtDNA copy number of compact cells was positively correlated with urinary free cortisol (UFC) (P=0.0428) and plasma cortisol (F) (P=0.0609). mtDNA copy number of clear cells were inversely correlated with F (0.0497). 4977 bp mtDNA deletion was more frequently detected in CPA (54%) and in adjacent ZF (50%) than in NFA (17%). Discussion Results of our present study did reveal that CPA harbored more senescent phenotype as demonstrated by abundant p16 and p21, marked telomere shortening, frequent mtDNA 4977bp deletion and relatively low mtDNA copy number, possibly caused by long-term exposure of excessive cortisol in situ compared to NFA. In addition, clear tumor cells could represent more senescent histological phenotype because of their lower mtDNA copy numbers. This is the first study to demonstrate that compact tumor cells were biologically more active than clear tumor cells and could reflect clinical cortisol biosynthesis, resulting in marked functional intratumoral heterogeneity in CPAs.